2016
DOI: 10.1111/tid.12501
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tuberculosis after kidney transplantation in a developing country

Abstract: TB continues to be a great challenge in KT, especially in developing countries, with significant impact on patient and graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 28 publications
7
41
1
1
Order By: Relevance
“…Early TB disease after transplantation in patients with or without isoniazid treatment, may even be due to unrecognized active disease at the time of transplantation or donor‐derived infection. Compared with Brazilian studies, TB incidence was somewhat lower . It is possible that the routine use of LTBI therapy for at‐risk patients might be the reason for this finding.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Early TB disease after transplantation in patients with or without isoniazid treatment, may even be due to unrecognized active disease at the time of transplantation or donor‐derived infection. Compared with Brazilian studies, TB incidence was somewhat lower . It is possible that the routine use of LTBI therapy for at‐risk patients might be the reason for this finding.…”
Section: Discussioncontrasting
confidence: 54%
“…Our data showed a significant increase in serum Cr during and after TB diagnosis and, consequently, a high prevalence of AKI, including the severe forms. Graft dysfunction has been previously described in other TB cohorts, but little has been reported about the causes of AKI . In our study, prerenal azotemia, sepsis, AR, and drug nephrotoxicity were the main identified causes of graft dysfunction.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The overall incidence of TB was 1.69% (range, 0.027‐13.27). Twenty‐nine studies provided incidence of TB among kidney‐only recipients, while 13 studies provided kidney recipient information in combination with other SOT data.…”
Section: Resultsmentioning
confidence: 99%
“…The use of CD4‐depleting agents such as muromonab (OKT‐3) or alemtuzumab (anti‐CD52) was detailed in 13 of 38 (34.21%) case reports, but this was not specified in others. Only 7 cohort studies reported on the use of these agents …”
Section: Resultsmentioning
confidence: 99%